2010
DOI: 10.1186/1476-0711-9-31
|View full text |Cite
|
Sign up to set email alerts
|

The dissemination of ST80-SCCmec-IV community-associated methicillin resistant Staphylococcus aureus clone in Kuwait hospitals

Abstract: BackgroundCommunity-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) is a global healthcare problem. The purpose of this study was to characterize CA-MRSA clones and their distribution in Kuwait hospitals.MethodsIn total, 135 CA-MRSA isolates, carrying the SCCmec IV or V genetic elements, isolated in eight hospitals were characterized using antibiogram, pulsed-field gel electrophoresis, multilocus sequence typing, and carriage of genes for Panton-Valentine Leukocidin (PVL), capsular polysacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 33 publications
(62 reference statements)
2
22
2
Order By: Relevance
“…However, all ST97 isolates reported so far have lacked genes for PVL. The only PVL-gene-positive isolate in this study was obtained from a patient in a different ward and was an ST80 clone which has been reported previously in Kuwait hospitals (Udo et al, 2008;Udo & Sarkhoo, 2010). Whereas the ST97-MRSA-SCCmec-V isolates reported in the UK contained the ACME genes (Ellington et al, 2008), those reported in this study were negative.…”
Section: Resultscontrasting
confidence: 47%
“…However, all ST97 isolates reported so far have lacked genes for PVL. The only PVL-gene-positive isolate in this study was obtained from a patient in a different ward and was an ST80 clone which has been reported previously in Kuwait hospitals (Udo et al, 2008;Udo & Sarkhoo, 2010). Whereas the ST97-MRSA-SCCmec-V isolates reported in the UK contained the ACME genes (Ellington et al, 2008), those reported in this study were negative.…”
Section: Resultscontrasting
confidence: 47%
“…6,7 This clone is also known to be frequent in North African and Middle East countries such as Tunisia, Jordan, and Kuwait. 1,17,31 However, the heterogeneity of the MRSA strains isolated in this study was to some extent a surprising finding compared to the large predominance of ST80-IV in the preceding investigations. Noteworthy, the two tst1 positive ST22-MRSA-IV strains, spa type t223, appeared to be similar to the ''Gaza strain,'' the predominant MRSA clone in healthy children and their parents living in the Gaza strip.…”
Section: Discussioncontrasting
confidence: 49%
“…Twenty-five allelic profiles were generated with the most prevalent STs being ST80 (4/36; 11%) and ST30 (3/ 36; 8%), which is in agreement with previous results from Lebanon, Jordan, Kuwait, and other neighboring countries. 10,33,[39][40][41] Clustering SCCmec with MLST identified seven MRSA and 20 MSSA clones, with PVL-positive ST80-MRSA-IV being the dominant clone (9/36; 7%), followed by PVL-positive ST30-MSSA (7/36; 5%) ( Table 3). The predominance of the ST80 clone has previously been reported in the region, 33,[39][40][41][42] while ST30-MSSA, known as the Southwest Pacific clone, has been shown to prevail in other areas, in particular Kuwait, Abu Dhabi, the UK, Germany, and Australia, 2 and to probably have been introduced through air travel.…”
Section: Resultsmentioning
confidence: 99%